PROSPECTS FOR THE INTRODUCTION OF ISLAMIC FINANCIAL SERVICES TO THE COUNTRY’S FINANCIAL AND CREDIT SYSTEM (American Journal of Business Management, Economics and Banking, 2025)
The article discusses the features of the development of the Islamic financial sector, the principles of the Islamic financial institutions, as well as financial instruments that are used within the Islamic financial system. The distinctive features of Islamic and traditional banks are analyzed and the current state of development of Islamic finance in the global economy was studied. In addition, the main directions of the development of Islamic finance in the Republic of Uzbekistan are presented.